Pengaruh Intensitas Kerja dan Efektivitas Kerja terhadap Kinerja Karyawan PT Sinar Alam Permai Palembang - Desti Tantiana; Roswaty Roswaty; Shafiera Lazuarni (Jurnal EMT KITA, 2026)
This study aims to determine the effect of work intensity and work effectiveness on employee performance at PT Sinar Alam Permai Palembang. This study uses a quantitative approach. Sampling uses the Slovin Technique, by calculating the number of samples needed in a large and limited population with the Slovin formula. The sample used was 222, the sampling technique used random sampling. Data obtained through questionnaire distribution were processed using IBM SPSS version 25.0 with multiple linear regression analysis techniques. The results of hypothesis testing indicate that the work intensity variable has a significant effect on employee performance. Meanwhile, the work effectiveness variable has a positive and significant effect on employee performance partially. The influence of the independent variables on the dependent variable can be significantly influenced.